Low-Dose Dexmedetomidine Attenuates the Dose Requirement of Propofol for Suppression of Body Movement in Patients Undergoing Operative Hysteroscopy - Zhang XF; Xiao F; Lou YY; Wu KW; Qian J; Zhu GW (Drug Design, Development and Therapy)
Xu-Feng Zhang,1 Fei Xiao,2 Ying-Ying Lou,1 Ke-Wei Wu,1 Jing Qian,2 Guo-Wei Zhu3 1Department of Anesthesia, the Affiliated LiHuiLi Hospital of Ningbo University, Ningbo Medical Center LiHuiLi Hospital, Ningbo City, People’s Republic of China; 2Department of Anesthesia, Jiaxing University Affiliated Women and Children Hospital, Jiaxing City, People’s Republic of China; 3Department of Anesthesia, Haining Maternal and Child Health Care Hospital, Haining City, People’s Republic of ChinaCorrespondence: Jing Qian, Department of Anesthesia, Jiaxing University Affiliated Women and Children Hospital, Jiaxing City, People’s Republic of China, Email 327597227@qq.com Guo-Wei Zhu, Department of Anesthesia, Haining Maternal and Child Health Care Hospital, Haining City, People’s Republic of China, Email Zhuweir@126.comBackground: Dexmedetomidine is a central α-2 adrenergic agonist characterized by its sedative, analgesic, and sympatholytic properties. We investigated the effect of low dose dexmedetomidine on the dose-response relationship of propofol for sedation in patients undergoing operative hysteroscopy.Methods: The patients were firstly randomly assigned to receive either propofol and fentanyl (P group, n = 100) or a combination of propofol, dexmedetomidine, and fentanyl (DP group, n = 100). Subsequently, participants were further randomized to receive propofol at doses of 1.0, 1.5, 2.0, and 2.5 mg/kg in P group, and 0.5, 1.0, 1.5, and 2.0 mg/kg in DP group. The primary outcome of this study was the incidence of patients achieving effective propofol dose, defined as the dosage at which a patient exhibited no body movement during cervical dilation and had a BIS value below60. The Probit method was used to calculate the ED50 and ED95 of propofol in the inhibition of body movement reaction to cervical dilation during hysteroscopic surgery.Results: The ED50 and ED95 values for propofol in the inhibition of body movement reaction to cervical dilation during hysteroscopic surgery were 1.781 (95% CI 1.507~2.118) and 4.670 (95% CI 3.555~7.506) mg/kg, respectively, in P group; while in the DP group, these values were found to be 0.983 (95% CI 0.800~1.173) and 2.578 (95% CI 2.013~3.895) mg/kg.Conclusion: Low-dose dexmedetomidine (0.5μg/kg) could reduce the requirement of propofol for suppression of body movement in patients undergoing operative hysteroscopy.Keywords: dexmedetomidine, propofol, cervical dilation, hysteroscopy, dose-response